Low Lactobacilli abundance and polymicrobial diversity in the lower reproductive tract of female rhesus monkeys do not compromise their reproductive success. Issue 10 (12th September 2017) - Amaral, Wellington Z.; Lubach, Gabriele R.; Kapoor, Amita; Proctor, Alexandra; Phillips, Gregory J.; Lyte, Mark; Coe, Christopher L.
Abstract : The lower reproductive tract of nonhuman primates is colonized with a diverse microbiota, resembling bacterial vaginosis (BV), a gynecological condition associated with negative reproductive outcomes in women. Our 4 aims were to: (i) assess the prevalence of low Lactobacilli and a BV‐like profile in female rhesus monkeys; (ii) quantify cytokines in their cervicovaginal fluid (CVF); (iii) examine the composition and structure of their mucosal microbiota with culture‐independent sequencing methods; and (iv) evaluate the potential influence on reproductive success. CVF specimens were obtained from 27 female rhesus monkeys for Gram's staining, and to determine acidity (pH), and quantify proinflammatory cytokines. Based on Nugent's classification, 40% had a score of 7 or higher, which would be indicative of BV in women. Nugent scores were significantly correlated with the pH of the CVF. Interleukin‐1ß was present at high concentrations, but not further elevated by high Nugent scores. Vaginal swabs were obtained from eight additional females to determine microbial diversity by rRNA gene amplicon sequencing. At the phylum level, the Firmicutes/Bacteroidetes ratio was low. The relative abundance of Lactobacilli was also low (between 3% and 17%), and 11 other genera were present at >1%. However, neither the microbial diversity in the community structure, nor high Nugent scores, was associated with reduced fecundity. Female monkeys provide an opportunity to understand how reproductive success can be sustained in the presence of a diverse polymicrobial community in the reproductive tract. Abstract : Of 27 female rhesus monkeys, 40% had a Nugent's score of 7 or higher, which would be indicative of BV in women. Nugent scores were significantly correlated with the pH of the CVF, but not associated with reduced fertility. Interleukin‐1ß was present at high concentrations, but not associated with Nugent scores. Vaginal microbiota profiles exhibited low Lactobacilli abundance as well as lowFirmicutes/Bacteroidetes ratio, but were also not associated with fertility.